Toxicity effect of Nigella sativa on the liver function of rats. - Dollah, Mohammad Aziz; Parhizkar, Saadat; Abd Latiff, Latiffah; Hassan, Mohamad Hafanizam (Tabriz University of Medical Sciences and Health Services, 2013)
Purpose: The aim of this study was to determine the toxic effect of Nigella sativa powder on the liver function which was evaluated by measuring liver enzymes and through histopathological examination of liver tissue.